2012
DOI: 10.1186/1757-4749-4-23
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cytokines in different organs after intranasal inoculation of Campylobacter jejuni in mice

Abstract: BackgroundCytokine production and histopathological changes occur in the lungs of mice after intranasal inoculation with Campylobacter jejuni, but the levels of cytokines in different organs to which C. jejuni disseminates have not been studied.FindingsAdult BALB/c mice were intranasally inoculated with C. jejuni 81–176 (test) or phosphate-buffered saline (control) (n=16 per group). The levels of cytokines in the organs (spleen, liver, and small and large intestines) to which C. jejuni disseminated were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…This indicates that changes in the host’s immune status may have an important impact in C. jejuni infection. It has been reported that TNF-α, IL-1, IL-4, and IL-10 are all elevated in mice after C. jejuni infection ( Al-Banna et al, 2012 ). In this study, co-infection of T. gondii and C. jejuni further increased the levels of IFN-γ and IL-6 caused by T. gondii , much in the same way as the changes in cytokines induced by C. jejuni in gnotobiotic mice ( Bereswill et al, 2011 ), which suggests that T. gondii infection promotes C. jejuni infection symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that changes in the host’s immune status may have an important impact in C. jejuni infection. It has been reported that TNF-α, IL-1, IL-4, and IL-10 are all elevated in mice after C. jejuni infection ( Al-Banna et al, 2012 ). In this study, co-infection of T. gondii and C. jejuni further increased the levels of IFN-γ and IL-6 caused by T. gondii , much in the same way as the changes in cytokines induced by C. jejuni in gnotobiotic mice ( Bereswill et al, 2011 ), which suggests that T. gondii infection promotes C. jejuni infection symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This is partly in agreement with cellular investigations of C. jejuni which supports a transcellular translocation. 5 Similarly, there is agreement with findings from pregnant guinea pig studies, where C. jejuni IA3902 was identified within the cytoplasm of trophoblasts, within phagocytes, in extracellular spaces surrounding trophoblasts in areas of placentitis and necrosis and occasionally surrounding uteroplacental arteries. 7 The presence of C. jejuni within murine trophoblasts and vasculature of the fetoplacental unit is also consistent with what has been described in sheep where the organism has been detected within trophoblasts and blood vessels of infected ovine placenta.…”
Section: Exudation Of Leukocytes Is a Feature Of The Reproductive Trasupporting
confidence: 86%
“…7 IL1β was found to act as a mediator of endothelial cell function and the placenta contributed to elevation in serum levels within the maternal circulation. 5 While the placenta was thought to produce small quantities of IL1β, trophoblasts can be induced to produce significant quantities of bioactive IL1β in vitro via endotoxin stimulation as evidenced by increased m RNA expression. 25 High levels of IL10 mRNA were expressed in trophoblasts with lesser quantities from the endometrial mucosa.…”
Section: Rnascope ® Resultsmentioning
confidence: 99%
See 2 more Smart Citations